Digital Based Learning Management With A Multimodal Approarch - Lestari, Ambar Sri (JURNAL AL-TANZIM, 2022)
The purpose of this study is to examine digital-based learning management with a multimodal approach to transform teaching materials. This study involved a multimodal approach to meaning interpretation, applying three metafunction principles: ideational (representational), interpersonal (social relations), and textual (organizing text). Such three metafunctions are combined with text, image, sound, and video tutorial modes in teaching materials. This study included twelve students willing to answer five open-ended questions about digital teaching materials via Google forms. The study's findings identified student feedback assessing digital teaching materials, specifically: 1) teaching materials packaged in ebook creator; 2) integration of multimedia in teaching materials; 3) integration of digital storytelling in teaching materials; and 4) material by the lesson plan. This study has implications for digital-based teaching to transmit innovative and diverse knowledge.